Pengembangan Modul Refleksi Implementasi Metode Gasing Berbasis Pendekatan Multimodalitas sebagai Upaya Continuing Professional Development bagi Guru - Eriya Gusmara; Dede Margo Irianto; Prihantini (Attractive : Innovative Education Journal, 2026)
This study aims to develop a reflection module for the implementation of the GASING method based on a multimodal approach as an effort to support teachers’ Continuing Professional Development (CPD). This research employed a qualitative descriptive approach supported by quantitative data, involving 100 school teachers who are familiar with or have implemented the GASING method. Data were collected through open-ended and closed questionnaires exploring teachers’ understanding of GASING principles, mastery of instructional steps, materials perceived as most difficult, the level of classroom implementation, encountered obstacles, school support, module needs, attitudes toward the GASING method, and suggestions for further development. Data analysis was conducted descriptively through frequency and percentage distributions as well as thematic categorization. The findings indicate that the majority of teachers demonstrate a moderate level of understanding of GASING principles and mastery of its instructional procedures, with varying levels of classroom implementation. The main challenges in implementing the method are related to the limited availability of teaching aids, time constraints in classroom instruction, and both students’ and teachers’ levels of understanding. Teachers generally expressed positive attitudes toward the GASING method and demonstrated a strong need for a reflection module that is comprehensive, interactive, and structured in progressive stages, supported by multimodal media such as instructional videos and practical guides. These findings highlight the urgency of developing a multimodal-based reflection module for the implementation of the GASING method as a contextual, sustainable, and practice-oriented professional learning resource to strengthen the implementation of teachers’ CPD in a more meaningful way.